Spectroscopic, quantum chemical, and topological calculations of the phenylephrine molecule using density functional theory - Mukesh Khadka; Manoj Sah; Raju Chaudhary; Suresh Kumar Sahani; Kameshwar Sahani; Binay Kumar Pandey; Digvijay Pandey (Scientific Reports)
Abstract In this work, Density Functional Theory (DFT) on Gaussian 09 W software was utilized to investigate the phenylephrine (PE) molecule (C9H13NO2). Firstly, the optimized structure of the PE molecule was obtained using B3LYP/6-311 + G (d, p) and CAM-B3LYP/6-311 + G (d, p) basis sets. The electron charge density is shown in Mulliken atomic charge as a bar chart and also as a color-filled map in Molecular Electrostatic Potential (MEP). Using these properties, the possibility of different charge transfers occurring within the molecule was evaluated. The calculated values of the energy gap from HOMO-LUMO mapping, illustrated in Frontier Molecular Orbitals (FMO) and Density of State (DOS), were found to be similar for both the neutral and anion states in the gaseous and water solvent phases. Both the global and local reactivity were studied to understand the reactivity of the PE molecule. Using the thermodynamic parameters, the thermochemical property of the title molecule was understood. Non-covalent interaction was studied to understand the Van der Waals interactions, hydrogen bonds, and steric repulsion in the title molecule. Natural Bond Orbital (NBO) Analysis was performed to understand the strongest stabilization interaction. In the vibrational analysis, Total Electron Density (TED) assignments were done in the intense region where the frequency of the title molecule was shifted distinctly. For vibrational spectroscopy, FT-IR and Raman spectra in the neutral and anion states were plotted and compared. Using the TD-DFT technique, the UV-Vis spectra along with Tauc’s plot were studied. Finally, topological analysis, electron localized function (ELF), and localized orbital locator (LOL) were performed in the PE molecule.